Early radiographic and clinical results of Salto total ankle arthroplasty as a fixed-bearing device. Issue 2 (June 2015) - Chao, John; Choi, Jae Hyuck; Grear, Benjamin J.; Tenenbaum, Shay; Bariteau, Jason T.; Brodsky, James W.
Highlights Study evaluates early radiographic and clinical results of Salto fixed bearing design. Significant improvements in clinical outcome scores at an average of 3 years followup. Survivorship of implant was 82.6% with any reoperation as endpoint. Survivorship of implant was 95.6% for revision or removal of components. Results are comparable to published outcomes and for mobile-bearing Salto design.